2016
DOI: 10.4103/jisp.jisp_328_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of two subgingival irrigating solutions in the management of periodontal disease: A clinicomicrobial study

Abstract: Context:Local administration of antimicrobial agents offer a “site-specific” approach to the periodontal therapy and it has several benefits.Aim:The present study was aimed to assess the clinical and microbial changes by subgingival irrigation using different subgingival irrigants in periodontitis patients and also to assess the mechanical effect of different local irrigation devices; if any.Settings and Design:Split-mouth design was employed on ten individuals.Materials and Methods:The study sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…22 The reinforcement of oral hygiene instructions and patient compliance added to the efficacy of the therapy. In contrast, Pandya et al 23 compared chlorhexidine with ozone water and concluded that chlorhexidine had a slight edge over ozonated water in terms of efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…22 The reinforcement of oral hygiene instructions and patient compliance added to the efficacy of the therapy. In contrast, Pandya et al 23 compared chlorhexidine with ozone water and concluded that chlorhexidine had a slight edge over ozonated water in terms of efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…'s vitro research, which demonstrated that dental plaque growth on decalcified human teeth was suppressed when exposed with ozonized water indicative of disinfecting properties, [11] further supports the findings of our investigation. When 0.2% chlorhexidine gluconate and ozonated water were used as subgingival irrigants, Pandya et al [12] found that chlorhexidine was more successful in improving the evaluated clinical and microbiological parameters. In contrast to the findings of our research, Seydanur Dengizek et al [13] observed no significant increase in periodontal repair with the use of ozone in their randomised controlled trial comparing ozone as an adjuvant to scaling and root planing.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were analyzed using the BANA-Zyme™ processor to assess periodontal pathogens of the "red complex". time varied widely from seconds (20-45) to minutes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Only in the study by Isler et al [29], surgical treatment for peri-implantitis was performed, and Amoxicillin (500mg) and Metronidazole (500mg) every 8 hours for 7 days were prescribed.…”
Section: Chaudhari Et Al (2016) [7]mentioning
confidence: 99%
“…For better control of the disease, periodontal treatment should be based on controlling the biofilm and the host response. The initial phase is the supraand subgingival mechanical debridement, which, although being the most important part of the treatment, cannot completely eliminate periodontal microorganisms, especially in very deep pockets (greater than 5-6mm) and furcation lesions [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation